Mid-Luteal 17-OH Progesterone Levels in 614 Women Undergoing IVF-Treatment and Fresh Embryo Transfer—Daytime Variation and Impact on Live Birth Rates - Thomsen, Lise Haaber; Humaidan, Peter; Erb, Karin; Overgaard, Martin; Andersen, Claus Yding; Kesmodel, Ulrik Schiøler (Frontiers in Endocrinology, 2018)
Introduction: Corpus luteum (CL) produces progesterone (P4) and 17-OH progesterone (17-OH P4) during the luteal phase. Contrary to P4, 17-OH P4 is not supplied as part of the luteal phase support following IVF- treatment. Therefore, measuring endogenous serum 17-OH P4 levels may more accurately reflect the CL function compared to monitoring serum P4 concentrations. Objective: To explore the correlation between mid-luteal serum 17-OH P4 levels and live birth rates and to explore the possible daytime variations in mid-luteal serum 17-OH P4. Design: Prospective cohort study. Patients: 614 women undergoing IVF-treatment and fresh embryo transfer. Intervention: All patients had serum 17-OH P4 measured seven days after oocyte pick-up (OPU+7). Furthermore, on OPU+7, seven patients underwent repeated blood sampling during daytime to clarify the endogenous daytime secretory pattern of 17-OH P4. Outcome Measure: Live birth rate. Secondary outcome Measure: Daytime variation in serum 17-OH P4 levels. Results: The highest chance of a live birth was seen with mid-luteal 17-OH P4 between 6.0 to 14.0 nmol/l. The chance of a live birth was reduced below (RD -10%, p=0.07), but also above the optimal range for 17-OH P4 (RD -12%, p=0.04). Patients with diminished CL-function (17-OH P4 <6 nmol/l) displayed clinically stable 17-OH P4 values, whereas patients with 17-OH P4 levels >6 nmol/l showed random 17-OH P4 fluctuations during daytime. Conclusion: The association between 17-OH P4 and reproductive outcomes is non-linear, and the negative effect of excessive CL-secretion seems to be just as strong as the negative effect of a reduced CL-function during the peri-implantation period.